2011
DOI: 10.1097/mog.0b013e32834baa4d
|View full text |Cite
|
Sign up to set email alerts
|

Probiotics and immune health

Abstract: Purpose of review The beneficial effects of probiotics have been demonstrated in many diseases. One of the major mechanisms of probiotic action is through the regulation of host immune response. This review highlights the recent scientific research findings that advance our understanding of probiotic regulation of the host immune response with potential application for disease prevention and treatment. Recent findings Probiotic genomic and proteomic studies have identified several genes and specific compound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
190
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 324 publications
(216 citation statements)
references
References 25 publications
3
190
0
7
Order By: Relevance
“…The gut microbiota 6 and certain probiotics 7 can promote the development of the intestinal barrier. Some specific probiotic strains altered the expression of tight junction proteins including occludin, cingulin, claudin-2 and ZO-2.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota 6 and certain probiotics 7 can promote the development of the intestinal barrier. Some specific probiotic strains altered the expression of tight junction proteins including occludin, cingulin, claudin-2 and ZO-2.…”
Section: Introductionmentioning
confidence: 99%
“…Probiotics are live microorganisms which, when consumed in adequate amounts as part of food, confer a health benefit on the host and may serve as a potential alternative therapy for disease prevention and treatment. Currently, both clinical and basic research has revealed several distinct cellular and molecular mechanisms underlying the beneficial effects of probiotics, including blocking pathogenic bacterial effects, regulating immune responses, and modulating intestinal epithelial homeostasis (3)(4)(5).…”
mentioning
confidence: 99%
“…В клинических и экспериментальных исследованиях показана эффективность пробиотиков при различных патологических состояниях, в том числе при диареях раз-личного генеза, проявлениях лактазной недостаточности у детей и взрослых, в послеоперационном периоде, при синдроме раздраженного кишечника и воспалительных заболеваниях кишечника [32][33][34]. …”
Section: механизм действия пробиотиковunclassified